The Relation Between Big Five Personality Traits and Relationship Formation Through Matchmaking - Liselotte Visser; Ron Pat-El; Johan Lataster; Jacques van Lankveld; Nele Jacobs (Psychology International, 2025)
Previous research has linked Big Five personality traits—agreeableness, openness to experience, neuroticism, extraversion, and conscientiousness—to relationship initiation in speed dating and relationship quality in long-term relationships. However, little is known about their role in matchmaking, where a matchmaker selects potential partners based on individual preferences and guides the dating process. This study examined whether the Big Five personality traits predict relationship formation in a matchmaking context. The sample included 1704 participants (48.5% men, 51.5% women; mean age = 62.5 years) living in the Netherlands. Personality was measured at baseline using the NEO-FFI questionnaire. Relationship formation success was defined as being in a relationship for at least three months. None of the Big Five traits predicted matchmaking success. Personality traits did not significantly predict relationship success in professionally guided matchmaking, suggesting that personality may play a limited role in this particular dating context.